PENGEMBANGAN e-LKPD INTERAKTIF MENGGUNAKAN PLATFORM LIVEWORKSHEET BERBASIS PENDEKATAN OPEN ENDED DI JURUSAN MATEMATIKA UNIVERSITAS NEGERI MEDAN - Purba, Glory Indira Diana; Suwanto, Fevi Rahmawati; Samosir, Katrina (MES: Journal of Mathematics Education and Science, 2024)
Research into the development of teaching materials in the form of interactive LKPD was motivated by students' lack of interest in working on mathematics problems other than those assigned by the lecturer. Therefore, they tend to be less able to solve a problem if given questions. With the LKPD, it is hoped that it will be able to train the development of cognitive aspects or all aspects of learning in the form of experimental guides or demonstrations. LKPD is a form of implementation by teachers who act as facilitators in learning. The application of LKPD can give students the opportunity to think actively and creatively to improve learning in achieving learning indicators and competencies. LKPD is given with the aim of actively involving students in learning activities, so that learning in the classroom is no longer teacher centered but student centered. For this reason, researchers use e-LKPD with the aim of making learning more fun and interactive. One of the advantages of e-LKPD is that it helps lecturers and students carry out learning independently at home because it can be accessed online without requiring face-to-face meetings. Apart from that, students can access text, image, audio and video content that cannot be contained in conventional LKPD. This research shows the following results: 1) the average validity given by media expert validators is 3.83 and material expert validators is 3.66, both of which are in the very valid category, 2) the practicality of the e-LKPD being developed is taken based on student response questionnaires. namely 92% which is in the very practical category, 3) the effectiveness of e-LKPD is obtained based on achieving classical completeness of 88.57% of students completing the material covered. given.